ʺLegal limits of the autonomy of institutions of higher education in the formation of educational programsʺ - Varych, O.; Savokhina, M. (Problems of Engineer-Pedagogical Education, 2022)
The paper considers the issues of formalization of legal norms aimed at regulating the internal quality assurance system of higher education through a system of local acts of specific higher education institutions. In particular, the normative legal acts of general nature concerning the regulation of this issue are analyzed, namely the Law “On Education”, the Law “On Higher Education”, the Regulations on Accreditation of Educational Programs for Training Higher Education Applicants, the Resolution of the Cabinet of Ministers “On Approval of the License Conditions for Educational Activities”. Significant attention is paid to studying the role of the National Agency for Quality Assurance in Higher Education in the process of forming a quality assurance system for higher education, in particular through the adoption of relevant regulations, the need for approval of which is clearly stated in the laws on education. An analysis of the gaps in normative regulations at the level of realization of powers of the Agency (NAZYAVO) is provided. Issues of local regulation of the internal quality assurance system of higher education are considered in more detail. First, the components of the system (VSZYAVO), which are set out in the law “On Higher Education”, are analyzed. There are some differences between the terminological expression of the components of the internal quality assurance system of higher education and the practice of organizing the educational process in higher education institutions. There is a discrepancy between certain legal categories, which leads to inaccuracies in their expression and ambiguous understanding at the level of specific higher education institutions. Secondly, the legal approaches of specific education institutions to the process of normative regulation of this group of public relations at the local level are considered in detail. Within each component of the internal quality assurance system (VSZYAVO) specific types of normative-legal acts, which fix legal norms, are allocated. Certain problems of substantive nature of local NLAs are revealed, as well as their inconsistency with each other, and the existence of quite a lot of them to regulate one and the same issue. The key problems in the process of application of legal technologies are analyzed, namely the lack of a systematic approach to the creation of local regulations, the lack of highly qualified professionals who are competent enough to develop legal acts.